Dollar Dominance and the Transmission of Monetary Policy - McLeay, Michael; Tenreyro, Silvana (Quarterly Journal of Economics, 2026)
Has the dominance of the dollar in global trade rendered monetary policy ineffective? An emerging view contends that if a country invoices its exports in dollars, exchange rates cannot stabilize economic activity, as the classical expenditure-switching channel is muted. This view rests on the premise that export prices are sticky in dollars, breaking the link between export demand and depreciations. But this assumption is not borne out by the data: goods priced in dollars tend to have more flexible prices, along with higher elasticities of substitution. We propose a model with more realistic assumptions and show that even with dollar pricing, depreciating the currency by loosening monetary policy can still boost exports and activity materially. The limit to any expansion is not demand, but supply capacity. We also show that low exchange rate pass-through to dollar prices is not informative about price stickiness. The price response to exchange rates is small when demand elasticities are high, even with flexible prices: low pass-through is an equilibrium result, not evidence of a nominal friction.